2012
DOI: 10.1186/1471-2458-12-579
|View full text |Cite
|
Sign up to set email alerts
|

Effect of survey instrument on participation in a follow-up study: a randomization study of a mailed questionnaire versus a computer-assisted telephone interview

Abstract: BackgroundMany epidemiological and public health surveys report increasing difficulty obtaining high participation rates. We conducted a pilot follow-up study to determine whether a mailed or telephone survey would better facilitate data collection in a subset of respondents to an earlier telephone survey conducted as part of the National Birth Defects Prevention Study.MethodsWe randomly assigned 392 eligible mothers to receive a self-administered, mailed questionnaire (MQ) or a computer-assisted telephone int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 25 publications
0
8
0
3
Order By: Relevance
“…From October 2015 to March 2016, the research team in the Educatel Study randomly selected a group of schoolteachers to be interviewed by telephone, either while they were at school or at home, via prior scheduling. Training for the interviewers reinforced the necessary communications skills and attributes to guarantee safety and tranquility for the interviewees, avoid embarrassments, and deal with any distrust or suspicion that might arise in this type of survey 16 . The questions were read by the interviewer from a computer screen, which recorded the answers in digital format in real time so as to feed them continuously into the database.…”
Section: Sample and Data Collectionmentioning
confidence: 99%
“…From October 2015 to March 2016, the research team in the Educatel Study randomly selected a group of schoolteachers to be interviewed by telephone, either while they were at school or at home, via prior scheduling. Training for the interviewers reinforced the necessary communications skills and attributes to guarantee safety and tranquility for the interviewees, avoid embarrassments, and deal with any distrust or suspicion that might arise in this type of survey 16 . The questions were read by the interviewer from a computer screen, which recorded the answers in digital format in real time so as to feed them continuously into the database.…”
Section: Sample and Data Collectionmentioning
confidence: 99%
“…To collect data on antimicrobial use and stewardship practices on feedlots, the questionnaire used in this study was lengthy, complex and sought information that may be perceived as sensitive. Previous studies have demonstrated that respondents are more likely to disclose sensitive information in anonymous mailed questionnaires than in other survey methods . However, the length and complexity of a questionnaire are also known to substantially influence the response rate by creating a cognitive burden on potential respondents.…”
Section: Discussionmentioning
confidence: 99%
“…The supervisor monitored the quality of the interviews by listening to the recordings and identifying tendencies, lapses, etc., which (when identified) were corrected immediately to decrease the measurement bias. Selection and training of the interviewers before the data collection began emphasized the importance of empathy, listening skills, capacity to answer the teacher's doubts without generating insecurity in communicating the survey's objectives 40 .…”
Section: Telephone Interviewmentioning
confidence: 99%